Lily's pesky plant - Larsen, Kirsten; Clarke, Judith (New York : Random House, 2006)
Lily, a garden-talent fairy, finds an unusual seed in the forest, plants it in her garden, and hopes that she will not be forced to uproot the plant it produces
"A Stepping Stone book."
Keywords: Fairies -- Fiction; Plants -- Fiction; Gardens -- Fiction